Ultrasound microbubble destruction imaging in acute middle cerebral artery stroke - Kern, Rolf; Perren, Fabienne; Schöneberger, Katrin; Gass, Achim; Hennerici, Michael G.; Meairs, Stephen (Stroke, 2004)
BACKGROUND AND PURPOSE: Cerebral perfusion imaging in acute stroke assists in determining the subtype and the severity of ischemia. Recent studies in perfusion models and in healthy volunteers have shown that ultrasound perfusion imaging based on microbubble destruction can be used to assess tissue perfusion. We applied ultrasound microbubble destruction imaging (MDI) to identify perfusion deficits in patients with acute middle cerebral artery (MCA) territory stroke. - METHODS: Fifteen acute MCA stroke patients with sufficient transtemporal bone windows were investigated with ultrasound MDI and perfusion-weighted MRI (PWI). MDI was performed using power pulse-inversion contrast harmonic imaging. Thirty seconds after a bolus injection of the echo contrast agent SonoVue, microbubbles were destroyed using a series of high-energy pulses. Local perfusion status was analyzed in selected regions of interest by destruction curves and acoustic intensity differences (DeltaI) before and after microbubble destruction. Local perfusion status was then compared with perfusion compromise as identified on PWI. - RESULTS: The mean differences of acoustic intensity from the ischemic MCA territory were significantly diminished compared with the normal hemisphere (DeltaI=2.52+/-1.75 versus DeltaI=13.79+/-7.31; P<0.001), resulting in lower slopes of microbubble destruction. PWI confirmed perfusion changes in the selected anatomical regions on time-to-peak maps in all 15 patients. - CONCLUSIONS: MDI is a qualitative method that can rapidly detect perfusion changes in acute stroke. When combined with other ultrasound techniques and PWI, it may well be valuable in the care of stroke unit patients, eg, as a screening method and for follow-up assessments of perfusion deficits.
Gesehen am 19.05.2022